Praktik Kepemimpinan Islam pada Organisasi Bisnis di Kota Gorontalo - Andi Mardiana (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
In applying the Islamic leadership in business organizations in the city of Gorontalo has a chance, because it is supported by the people of the city of Gorontalo Muslim majority, who have a philosophy in the local language